2017
DOI: 10.1089/acm.2016.0289
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicine Use and Its Association with Emotional Status and Quality of Life in Patients with a Solid Tumor: A Cross-Sectional Study

Abstract: Objectives: Complementary and alternative medicine (CAM) has been used widely in various populations for various purposes, including emotional support and improvement of quality of life (QOL). However, CAM use and purposes for using CAM are less clear among Korean patients with a solid tumor. The purpose of this study was to determine the prevalence and type of CAM use, and the association between CAM use and anxiety, depression, and QOL in patients with a solid tumor.Design: A cross-sectional survey.Setting: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 52 publications
4
43
2
Order By: Relevance
“…In our study, CAM users had higher depression scores than nonusers. Research in the general population indicates that CAM users are more often suffering from depression than nonusers . The high rate of comorbidity of depression and anxiety disorders among MS patients could be one cause for the frequent use of CAM in MS.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, CAM users had higher depression scores than nonusers. Research in the general population indicates that CAM users are more often suffering from depression than nonusers . The high rate of comorbidity of depression and anxiety disorders among MS patients could be one cause for the frequent use of CAM in MS.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of CAM usage was reported per week. Additionally, our study focused on herbal medicine due to a high incidence of reported usage among the different populations [ 13 , 61 63 ]. In the fourth section, respondents were asked to provide reasons for using CAM in self-therapy practices using closed-ended questions.…”
Section: Methodsmentioning
confidence: 99%
“…The reports on the utilization of CAM in South Korea (hereafter Korea) through 2011 have been reviewed by Kim SG et al [ 1 ]. There have also been several other reports since 2011 [ 2 11 ]. However, most studies either report on the utilization of CAM in patients with specific diseases (e.g., cancer) or provide an indirect report.…”
Section: Introductionmentioning
confidence: 94%